An Extreme Wave Event in eastern Yucatán, Mexico: evidence of a paleotsunami event during the Mayan times. - Lario, Javier; Spencer, Chris; Bardají, Teresa; Marchante, Ángel; Garduño-Monroy, Víctor H.; Macías-Sánchez, Jorge; Ortega-Acosta, Sergio (Wiley, 2019)
La península de Yucatán, México, ha sido considerada una región tectónicamente estable sin actividad sísmica significativa, aunque está regularmente afectada por huracanes. Un estudio detallado de aproximadamente 100 km de la costa este de Yucatán y Cozumel identificó crestas que contienen bloques de más de 1 m, alcanzando hasta cinco metros de altura, asociadas con Eventos de Oleaje Extremo (EWE). Los modelos de tsunami de zonas sísmicas conocidas en la región (Cinturón de Cabalgamiento de Muertos y Cinturón Deformado del Sur del Caribe) no son de escala suficiente para haber producido estas crestas. Los huracanes más destructivos (Gilbert 1988 y Wilma 2005) produjeron olas demasiado pequeñas para crear estas estructuras. Este estudio presenta un nuevo modelo de tsunami que indica que un evento de tsunami pudo haber causado el EWE responsable de la deposición de las crestas de bloques.

The Yucatán Peninsula, Mexico, has typically been considered a tectonically stable region with little significant seismic activity. The region though, is one that is regularly affected by hurricanes. A detailed survey of ca 100 km of the eastern Yucatán and Cozumel coast identified the presence of ridges containing individual boulders measuring >1 m in length. The boulder ridges reach 5 m in height and their origin is associated with extreme wave event activity. Previously modelled tsunami waves from known seismically active zones in the region (Muertos Thrust Belt and South Caribbean Deformed Belt) are not of sufficient scale in the area of the Yucatán Peninsula to have produced the boulder ridges recorded in this study. The occurrence of hurricanes in this region is more common, but two of the most destructive (Hurricane Gilbert 1988 and Hurricane Wilma 2005) produced coastal waves too small to have created the ridges recorded here. In this paper, a new tsunami model with a source area located on the Motagua/Swan Island Fault System has been generated that indicates a tsunami event may have caused the extreme wave events that resulted in the deposition of the boulder ridges.
https://openpolicyfinder.jisc.ac.uk/id/publication/7707
Keywords: Maremotos; Sismología - Yucatán (Península); Tsunami-HySEA; Arqueosismología; Tsunami; Paleosismología